2011
DOI: 10.1128/jcm.00956-10
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Field Gel Electrophoresis Genotyping of Taylorella equigenitalis Isolates Collected in the United States from 1978 to 2010

Abstract: Taylorella equigenitalis is the etiologic agent of contagious equine metritis (CEM), a venereal disease of horses. A total of 82 strains of T. equigenitalis isolated in the United States were analyzed by pulsed-field gel electrophoresis (PFGE) after digestion of genomic DNA with restriction enzyme ApaI. Twenty-eight of those strains isolated from horses in the 2009 U.S. outbreak (CEM09) were further analyzed with NotI and NaeI enzymes. When ApaI alone was used for analysis, the 82 isolates clustered into 15 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…CEM was first reported in 1977 in the United Kingdom and Ireland among Thoroughbred horses (Crowhurst, 1977;Timoney et al, 1977), but is currently a worldwide concern in various equine breeds (Jeoung et al, 2016;Schulman et al, 2013) with the hypothesis that the episodic "source of contagion" is often mainland Europe (Schulman et al, 2013). Pulsedfield gel electrophoresis (Aalsburg and Erdman, 2011;Sting et al, 2016) and several other molecular typing tools including field inversion gel electrophoresis (Bleumink-Pluym et al, 1990), chromosomal DNA fingerprinting (Thoresen et al, 1995), crossed-field gel electrophoresis (Miyazawa et al, 1995) and more recently repetitive extragenic palindromic PCR (Sting et al, 2016) have been used to genotype CEM isolates. However, these molecular epidemiological tools are not very portable and inter-laboratory results are difficult to compare (Maiden et al, 1998), making them ill-suited for global epidemiological studies of 5 CEM outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…CEM was first reported in 1977 in the United Kingdom and Ireland among Thoroughbred horses (Crowhurst, 1977;Timoney et al, 1977), but is currently a worldwide concern in various equine breeds (Jeoung et al, 2016;Schulman et al, 2013) with the hypothesis that the episodic "source of contagion" is often mainland Europe (Schulman et al, 2013). Pulsedfield gel electrophoresis (Aalsburg and Erdman, 2011;Sting et al, 2016) and several other molecular typing tools including field inversion gel electrophoresis (Bleumink-Pluym et al, 1990), chromosomal DNA fingerprinting (Thoresen et al, 1995), crossed-field gel electrophoresis (Miyazawa et al, 1995) and more recently repetitive extragenic palindromic PCR (Sting et al, 2016) have been used to genotype CEM isolates. However, these molecular epidemiological tools are not very portable and inter-laboratory results are difficult to compare (Maiden et al, 1998), making them ill-suited for global epidemiological studies of 5 CEM outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Missed diagnoses of animals, especially those that are asymptomatic, leaves countries vulnerable to new introductions. These introductions pose a great risk for countries where the organism is not endemic, like the United States, and are key to the insidious movement of the organism throughout the world [ 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further research showed that in all 109 Japanese isolates between 2 studies there was a single, identical electrophoresis pattern with pulsed-field gel-electrophoresis (PFGE), but these differed from strains originating in other parts of the world [ 9 , 10 ]. Despite these large groupings, PFGE provided the most distinguishing genetic characteristics among isolates for many years with studies showing as many as 17 groups in 82 isolates [ 6 ]. Other attempted methods, random amplified polymorphic DNA and amplified rDNA restriction analysis, made previously distinguishable isolates appear identical [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taylorella equigenitalis is a nonmotile, microaerophilic Gram‐negative, frequently pleiomorphic bacterium that causes contagious equine metritis (CEM), a nonsystemic, venereally transmitted disease of horses. T. equigenitalis is spread directly during natural mating or artificial insemination (AI) with semen from a carrier stallion and by indirect fomite transmission . Affected stallions are unapparent carriers of the organism and are the principal source of infection.…”
Section: Introductionmentioning
confidence: 99%